Design of a cyclone separator with circumfluent cyclone and convergent vortex finder for spray drying - Anis Aprilia (BKS-TM Indonesia, 2025)
Coconut milk is prone to spoilage due to its high-water content. Spray drying can extend its shelf life, but conventional cyclone separators often experience re-entrainment and high pressure drop. This study proposes a cyclone separator design with a Circumfluent Cyclone (CFC) structure and a Convergent Vortex Finder (CVF) to improve particle separation. The design was based on analytical calculations involving swirl number and vortex behavior. A prototype with a diameter of 0.11 meters was fabricated and tested under varying air flow rates from 10 to 30 cubic meters per hour and temperatures from 120 to 150 degrees Celsius. The results showed a particle collection efficiency of 100 percent and a minimum pressure drop of 569 pascals. However, this efficiency does not fully represent the actual performance of the cyclone separator because the particles entering the system were large, agglomerated, and oily, which did not match the intended design conditions. Despite this, the modified design successfully reduced reentrainment and improved flow stability.